2016
DOI: 10.1111/apm.12503
|View full text |Cite
|
Sign up to set email alerts
|

Incidental finding of multiple well‐differentiated papillary mesotheliomas in peritoneum

Abstract: We present a case of multiple well-differentiated papillary mesotheliomas (WDPM) in the peritoneum found incidentally in a 63-year-old man with urothelial carcinoma of the bladder. When multiple tumors are seen, malignant mesothelioma should be excluded by histopathological examination as this may have a similar focal appearance to WDPM. True stromal invasion is by far the most reliable criterion of mesothelial malignancy. In doubtful cases, a conservative diagnostic approach has been recommended. Compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Most cases of WDPM are incidentally detected as a small, single nodule during surgery for other causes. WDPM can also present as multiple lesions involving the pleural or peritoneal surfaces (10,11). WDPM typically shows an indolent clinical course (12); however, a few cases of recurrent WDPM have been reported (13).…”
mentioning
confidence: 99%
“…Most cases of WDPM are incidentally detected as a small, single nodule during surgery for other causes. WDPM can also present as multiple lesions involving the pleural or peritoneal surfaces (10,11). WDPM typically shows an indolent clinical course (12); however, a few cases of recurrent WDPM have been reported (13).…”
mentioning
confidence: 99%
“…There are only a few reports related to this topic in the current literature. Jacobsen et al reported a case of PM in a patient with non-muscle invasive urothelial carcinoma (10). The other published case reports only consist of gynecologic cancers (11).…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare, distinct tumor arising from mesothelial cells with papillary architecture, bland cytological features, and a tendency toward superficial spread without invasion . WDPM is typically found in the peritoneal cavity in women; however, it can also occur in the pleura, pericardium, and tunica vaginalis testis . WDPM is associated with an indolent clinical course and long survival, and is distinct from conventional diffuse malignant mesothelioma (MM).…”
mentioning
confidence: 99%
“…2,3 WDPM is typically found in the peritoneal cavity in women; however, it can also occur in the pleura, pericardium, and tunica vaginalis testis. [4][5][6][7][8][9] WDPM is associated with an indolent clinical course and long survival, and is distinct from conventional diffuse malignant mesothelioma (MM). Invasion is not typically observed in WDPM; however, rare cases show limited invasion, and are termed WDPM with invasive foci.…”
mentioning
confidence: 99%